Optimization of anodizing parameters for the morphological properties of TiO2 nanotubes based on response surface methodology - Hossen, Md Arif; Azrina, Abd Aziz; Ikreedeegh, Riyadh Ramadhan; Aamina, Din Muhammad; Nurashikin, Yaacof; Kah, Hon Leong; Wu, Lihua (Elsevier Ltd, 2024)
TiO2 nanotube (TNT) morphology is crucial for applications in a variety of fields. In this paper, response surface methodology (RSM) has been utilized to optimize the anodizing parameters i.e., electrolyte concentration (C), anodization voltage (V), and time (t) for morphology (e.g., nanotube diameter and length) of TNTs. Ethylene glycol (EG) based electrolyte has been used for anodization employing ammonium fluoride (NH4F) as a source of fluoride ion (F–) with 2.5 vol% H2O. Reliable regression models have been developed between the input variables and the corresponding responses, namely tube diameter and length with multiple regression coefficients of 0.9649 and 0.9253, respectively, revealing a trustworthy association between the actual and those predicted values using the quadratic model. The predicted values of C (0.31 wt%), V (38.44 V), and t (69.37 min) were found to be the optimum anodization condition preceding a TiO2 nanotubes diameter of 99.31 nm and length of 4572.64 nm. It was observed that the nanotubes diameter and length are more affected by anodizing voltage and time, and less sensitive to NH4F concentration. Therefore, RMS could be an appropriate technique to optimize anodizing parameters for producing TiO2 nanotubes with good morphology.